CREATION OF FAVORABLE EDUCATIONAL ENVIRONMENT IN THE HIGHER EDUCATION INSTITUTIONS OF UKRAINE - Kovalchuk, Vasyl; Marynchenko, Inna; Yashchuk, Sergii (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The current conditions of socio-economic development of Ukraine make changes in the conditions of functioning of higher education. The aim of the article is to investigate the state and identify the problems of creating a favorable educational environment in institutions of higher education. The main methods used are theoretical, empirical, diagnostic, graphic. The article thoroughly researches and substantiates theoretical and methodological foundations and develops the structure of creation of favorable educational environment for professional training of future teachers of vocational training. We have identified the following generally accepted indicators of a favorable educational environment: a favorable psychological climate; content of education, technology of training; spatial environment; development opportunities. 180 teachers from Glukhiv National Pedagogical University named after Alexander Dovzhenko, Khmelnitsky National University, and State Higher Educational Institution “University of Management of Education” participated in the study. Expert assessment of indicators of a favorable educational environment was carried out by teachers through questionnaires. To diagnose the level of favorable psychological climate in the team, we used the methodology of V.V. Shampalovsky and E.G. Shelest "Diagnosis of psychological climate in a small production group". And indicators for diagnosing indicators - content of education, technology of training, spatial environment, development opportunities were investigated by created by us author's questionnaires. The indicators were evaluated on a 5-point scale.